Answer:
=
−
5
Explanation:
−
8
−
3
(
2
+
1
)
=
6
7
-8x{\color{#c92786}{-3(2x+1)}}=67
−8x−3(2x+1)=67
−
8
−
6
−
3
=
6
7
-8x{\color{#c92786}{-6x-3}}=67
−8x−6x−3=67
2
Combine like terms
−
8
−
6
−
3
=
6
7
{\color{#c92786}{-8x}}{\color{#c92786}{-6x}}-3=67
−8x−6x−3=67
−
1
4
−
3
=
6
7
{\color{#c92786}{-14x}}-3=67
−14x−3=67
3
Add
3
3
3
to both sides of the equation
−
1
4
−
3
=
6
7
-14x-3=67
−14x−3=67
−
1
4
−
3
+
3
=
6
7
+
3−
1
4
=
7
0
-14x=70
−14x=70
5
Divide both sides of the equation by the same term
−
1
4
=
7
0
-14x=70
−14x=70
−
1
4
−
1
4
=
7
0
−
1
4
\frac{-14x}{{\color{#c92786}{-14}}}=\frac{70}{{\color{#c92786}{-14}}}
−14−14x=−1470
6
Simplify
Cancel terms that are in both the numerator and denominator
Divide the numbers
=
−
5